Epidemiology and prognostic factors for mycosis fungoides and Sézary syndrome in a multi‐ethnic Asian cohort: a 12‐year review. (27th March 2019) - Lim, H.L.J.; Tan, E.S.T.; Tee, S.I.; Ho, Z.Y.; Boey, J.J.J.; Tan, W.P.; Tang, M.B.Y.; Shen, L.; Chan, Y.H.; Tan, S.H.
Abstract: Background: Limited information exists regarding survival of Asian patients with mycosis fungoides (MF) and Sézary syndrome (SS). Objective: To evaluate the epidemiology, outcome and prognostic factors of these patients. Methods: A retrospective review of MF/SS cases diagnosed from 2000 to 2011 at a tertiary referral dermatology centre in Singapore was performed. Results: Of 246 patients, 63% were male and the median age at diagnosis was 49 years. 73.2% were Chinese, 12.6% Indian, 6.9% Malay and 7.3% Caucasian. A total of 239 patients (97.2%) had MF and seven had SS. Median follow‐up duration was 6.3 years, and median duration of symptoms at diagnosis was 13 months. For patients with MF, the majority had early disease (92.8% stage IA–IIA). 3.8% were stage IIB, 1.7% stage III and 1.7% stage IV. Complete response to treatment occurred in 78.2%, partial response in 9.6%, persistent but non‐progressive disease in 10.0% and disease progression in 4.1% of patients. Large cell transformation occurred in 4.1% of patients. Mean overall survival during this study was 12.7 years, with death occurring in 2.5% of patients (all ≥stage IIB at diagnosis). For patients with SS, 71.4% presented with stage IVA disease, 28.6% stage IVB. Complete response to treatment occurred in 14.2%, persistent but non‐progressive disease in 28.6% and disease progression in 57.2% of patients. Mean overall survival was 3.3 years within this study, with death occurring in 42.9% of SS patients. Prognostic factors associated with favourable recurrence‐free survival were male gender ( P  = 0.008), early disease stage (T1) at diagnosis ( P  < 0.001) and absence of maintenance treatment after remission ( P  = 0.01). Conclusion: Compared to Caucasian and East Asian cohorts, MF in South‐East Asians was diagnosed at a younger age and associated with lower mortality, largely due to greater prevalence of hypopigmented MF.